EFEK EKSTRAK ETANOL BIJI PEPAYA (Carica papaya linn) TERHADAP KADAR 17-β ESTRADIOL DAN FOLIKULOGENESIS PADA MENCIT BETINA (Mus musculus) - Puspitasari, Yenny (STRADA : Jurnal Ilmiah Kesehatan, 2012)
Indonesia is a developing country with population density problem occupies the fourth rank of the world. One effort made to suppress the population growth is through family planning. One of the efforts to succeed family planning is the development of raw materials from papaya for antifertility natural ingredients. The purpose of this research was to study the effects of ethanol papaya extract seeds on antifertility in female mice. The benefits of this research was to provide information about the use of ethanol papaya extract seeds as antifertility in animals and make ethanol extract of papaya seeds as an alternative contraceptive drug. This study used post-test only control group design. Samples were taken in random. The independent variable was ethanol papaya extract seeds in various doses. The dependent variables were folliculogenetic examination and the examination of 17-β estradiol levels. Data analysis to determine the different mean number of follicles and the levels of blood 17-β estradiol weer performed with one-way ANOVA test. Ethanol extract of papaya seeds in dose of 30 mg/kg, 100 mg/kg, 300 mg/kg lowered the number of tertiary and de Graaf follicles, while primary and secondary follicles did not decrease. The number of primary follicles are significantly different (p < 0,05).17-β estradiol in the dose group was decreasing along the increase of the doses. Levels of 17-β estradiol in blood showed significant differences (p < 0.05). The correlation between the number of primary, secondary, tertiary, and de Graaf follicles with 17-β estradiol levels were not statistically significant (p > 0.05) for the Pl, P2, P3, P4, P5. Ethanol extract of papaya seeds is proved to decrease the number of tertiary and de Graaf follicles in the ovary and decrease the levels of 17-β estradiol in blood, causing infertility in women.